Koenig and Schultz's disaster medicine : comprehensive principles and practice - Koenig, Kristi L.; Schultz, Carl H. (Carl Herman) (Cambridge : Cambridge University Press, 2016)
As societies become more complex and interconnected, the global risk for catastrophic disasters is increasing. Demand for expertise to mitigate the human suffering and damage these events cause is also high. A new field of disaster medicine is emerging, offering innovative approaches to optimize disaster management. Much of the information needed to create the foundation for this growing specialty is not objectively described or is scattered among multiple different sources. This definitive work brings together a coherent and comprehensive collection of scientific observations and evidence-based recommendations with expert contributors from around the globe. This book identifies essential subject matter, clarifies nomenclature, and outlines necessary areas of proficiency for healthcare professionals handling mass casualty crises. It also describes in-depth strategies for the rapid diagnosis and treatment of victims suffering from blast injuries or exposure to chemical, biological, and radiological agents.
Title from publisher's bibliographic system (viewed on 05 Apr 2016).
Keywords: Disaster medicine